APPLICATION OF SOFTWARE IN PROSTHETICS ON DENTAL IMPLANTS - Abduganieva, Sh.X.; Normirzaev , Sh.N.; Gaybullaeva, M.N. (Educational Research in Universal Sciences, 2023)
Today, the demand for dental implants is actively growing and at the same time the demand for high-quality prosthetics. In this article I want to introduce you to software and new technologies in the world of dentistry.